(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Antimullerian hormone (AMH) is a promising marker of polycystic ovary syndrome (PCOS) and polycystic ovarian morphology (PCOM). Limited data are available regarding its utility among Bangladeshi women with PCOS. Objectives: This study aimed to see the association between AMH and diagnostic markers of PCOS. Methods: This cross-sectional comparative study included 100 women with PCOS based on Rotterdam criteria and 78 matched healthy controls. Following the collection of clinical information, fasting blood was collected during the follicular phase of the menstrual cycle to measure total testosterone (TT), luteinizing hormone (LH), follicle-stimulating hormone (FSH) by chemiluminescence and AMH by ELISA method. An ultrasonogram of the ovaries was done either transvaginal or transabdominal route depending on the patient’s marital status. Results: Women with PCOS had higher AMH levels than controls [6.49 (2.31, 10.3) vs. 2.78 (1.38, 7.01), median (IQR), p<0.001). Among women with PCOS, AMH levels were lower with hyperandrogenemia (TT>4.6 ng/mL) than with normoandrogenemia [3.99 (2.0, 9.18) vs. 8.13 (4.84, 12.25), p=0.008]. AMH levels did not vary with the status of the menstrual cycle, hirsutism, PCOM, LH/FSH ratio (>2.0), and phenotypes of PCOS. AMH negatively correlated with TT among women with PCOS (ρ= -0.26, p= 0.010). Serum AMH was a poor marker of PCOS (AUC: 0.67) and not for PCOM at all. Conclusion: Serum AMH levels were higher in women with PCOS than controls with a negative association with TT. Serum AMH had little utility for the diagnosis of PCOS and PCOM. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2024; 3 (1): 16-21